A novel association between COMT and BDNF gene polymorphisms and likelihood of symptomatic dysphagia in older people. Issue 9 (14th June 2015) - Nimmons, D.; Pendleton, N.; Payton, A.; Ollier, W.; Horan, M.; Wilkinson, J.; Hamdy, S.
Abstract Background Catechol‐O‐methyl transferase (COMT) and brain‐derived neurotrophic factor (BDNF) are neuro‐modulatory proteins that have been demonstrated to affect cortical plasticity, which in turn has been shown to affect age‐related changes and neuronal functioning in humans. Here, we tested the hypothesis that single nucleotide polymorphisms (SNP) within COMT and BDNF genes are associated with dysphagia in older adults. Methods A total of 800 community‐dwelling older individuals were sent the Sydney Oropharyngeal Dysphagia Questionnaire to identify swallowing difficulties. DNA from this population was available for study and used to genotype 18 COMT and 12 BDNF polymorphisms. Logistic regression statistical models were used to identify potential associations between dysphagia and the genotypes. Key Results A total of 638 individuals completed the questionnaire, giving an 80% response rate. Of these, 538 were genotyped for COMT and BDNF polymorphisms. Age was found to predict dysphagia (p = 0.018, OR = 1.08, CI = 1.01–1.14). The COMT polymorphism rs165599 and the BDNF polymorphism rs10835211 were found to predict dysphagia and have an interactive effect (p = 0.028), which varied according to the carrier status of the other. In the case of SNP rs10835211, the effect of heterozygosity was protective or harmful dependent on the respective status of rs165599. Conclusions & Inferences These results suggest that certain interactions between plasticity genes contribute to the development of dysphagia with increasing age. This highlights a possible role for genetic factors in future monitoring and treating individuals affected by dysphagia.